Airway Pressure Release Ventilation in Acute Respiratory Distress Syndrome (Journal of the Bangladesh Society of Anaesthesiologists, 2022)
Background : Acute respiratory distress syndrome (ARDS) is characterized by a heterogeneous patternof diffuse alveolar damage resulting from either a direct, indirect, or a combination of insults to thelungs. The injured lung in acute respiratory distress syndrome (ARDS) is heterogeneous in gas andfluid distribution, depending upon the causes of ARDS.Objectives : To observe the effectiveness of airway pressure release ventilation in acute respiratorydistress syndrome.Materials & Methods: This was a prospective randomized controlled trial, was carried out in theDepartment of Anesthesiology, Analgesia, Palliative and Intensive Care Medicine, Dhaka MedicalCollege Hospital, Dhaka, Bangladesh carried out from the period January 2015 to December 2016,conducted with mechanically ventilated patients with acute respiratory distress syndrome at intensivecare unit, DMCH.Results: A total of 48 patients were enrolled in this study and they were divided into two groups. Eachgroup had 24 patients. PaO2, SpO2, mean airway pressure and PaO2/FiO2 were significantlyincreased (improved) in both groups but significantly higher in APRV group. PaCO2, FiO2 and peakinspiratory pressure were significantly decreased in both groups and significantly lesser in APRVgroup. Less sedation was required in APRV group.Conclusion: Airway pressure release ventilation is a better and acceptable method of ventilation inacute respiratory distress syndrome.JBSA 2022; 35 (1) : 46-56